2001
DOI: 10.1093/hmg/10.17.1721
|View full text |Cite
|
Sign up to set email alerts
|

Divergent evolution in M6P/IGF2R imprinting from the Jurassic to the Quaternary

Abstract: M6P/IGF2R imprinting first appeared approximately 150 million years ago following the divergence of prototherian from therian mammals. Although M6P/IGF2R is clearly imprinted in opossums and rodents, its imprint status in humans remains ambiguous. It is also still unknown if M6P/IGF2R imprinting was an ancestral mammalian epigenotype or if it evolved convergently. We report herein that M6P/IGF2R is imprinted in Artiodactyla, as it is in Rodentia and Marsupialia, but that it is not imprinted in Scandentia, Derm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
134
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(148 citation statements)
references
References 45 publications
11
134
3
Order By: Relevance
“…Nevertheless, gene sequencing and protein analysis are necessary to draw the conclusion that the ESX1L gene is not involved in IUGR. Discrepancy of the imprinting status of loci between humans and mice has already been reported for Igf2R/IGF2R; in an extensive study of seven placentas, 46 conceptuses and seven Wilm's tumors, Killian et al 35 found no evidence of imprinting of IGF2R in humans.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, gene sequencing and protein analysis are necessary to draw the conclusion that the ESX1L gene is not involved in IUGR. Discrepancy of the imprinting status of loci between humans and mice has already been reported for Igf2R/IGF2R; in an extensive study of seven placentas, 46 conceptuses and seven Wilm's tumors, Killian et al 35 found no evidence of imprinting of IGF2R in humans.…”
Section: Discussionmentioning
confidence: 98%
“…Second, it may be that bovine genes are not imprinted, not completely imprinted ('leaky' expression) or show tissuespecific temporal imprinting in adult tissues. IGF2R has been found previously to be imprinted in the mouse and cow (Killian et al 2001), but not in the human Yang et al 2003). There are also numerous genes that show imprinting in only a select number of tissues, such as PPP1R9A, which is maternally expressed in fetal muscle, eye and placenta but is biallelically expressed in other tissues (Nakabayashi et al 2004), OBPH1, which shows predominant maternal expression in the placenta but biallelic expression in fetal and newborn organs in the human and mouse (Higashimoto et al 2002), and KCNQ1, whose expression is imprinted in several tissues but not in the heart (Lee et al 1997).…”
Section: Genomic Imprinting Statusmentioning
confidence: 92%
“…The discordance in the Igf2r/Air region may reflect the lack of conservation of genomic imprinting between the mouse and human Igf2r genes. The human IGF2R gene shows a polymorphic type of imprinted expression that is limited to embryonic stages, whereas adult tissues have been reported to show only biparental expression (Xu et al 1993;Killian et al 2001). This contrasts to the maintenance of imprinted Igf2r expression in most tissues of the mouse embryo and adult (Braidotti et al 2004).…”
Section: Evolutionary Conservation Versus Unbiased Approachesmentioning
confidence: 98%
“…Because of the lack of conservation of imprinted expression between the mouse and human Igf2r genes (Xu et al 1993;Killian et al 2001), we used an unbiased approach to map candidate transcriptional regulators in the mouse Igf2r/Air region using DHS assays. DHS assays identify short regions of approximately 200-400 bp that are sensitive to the action of nucleases because of nucleosome displacement or altered chromatin structure.…”
mentioning
confidence: 99%